Financial Integration in Asset and Liability Holdings in East Asia - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2015)
In this paper, we examine the evolution of intra-East Asian financial integration from 2001 to 2013. Most existing studies on this topic look primarily at asset holdings; we examine liability holdings as well. Using the International Monetary Fund's Coordinated Portfolio Investment Survey data for equities, long-term debt, and short-term debt, our analysis generally supports the conventional wisdom that East Asian countries are more financially integrated with global financial centers than they are with each other. This is true for both asset holdings and liabilities and is confirmed by an econometric analysis based on financial gravity equations. However, the gap between global integration and regional integration has narrowed for asset holdings over time but not for liability holdings. The results of additional econometric analysis indicate that the diversification of liability holdings can mitigate financial instability due to global financial shocks. More precisely, diversification was associated with smaller exchange rate depreciation during the quantitative easing taper tantrum of 2013. These results point to a possible benefit from strengthening regional financial integration. Deeper regional integration would reduce dependence on global financial markets for funding and hence vulnerability to global shocks.
hdl:11540/5109
Keywords: F32; F44; G01; 330; East Asia; exchange rate depreciation; financial integration; financial stability; global integration; QE tapering; regional integration